Leading schools in a data-rich world. harnessing data for school improvement - Earl, Lorna M. (Lorna Maxine), 1948-; Katz, Steven (College teacher); Ben Jaafar, Sonia, 1974- (Corwin Press, 2008)
This facilitator's guide helps trainers build educators' understanding of data analysis, promote an inquiry ""habit of mind, "" and develop leaders' capacity to support an inquiry process.